Determination of the level of products novelty importance for developing product innovative policy - Fedulova, Irina; Dragan, Olena; Sheremet, Oleg; Vasyutinska, Julia; Berger, Alina (My University, 2021)
To substantiate the range of products of the enterprise there is a need to assess the potential of products in terms of the company’s ability to manufacture these products, consumer opportunities to meet their needs for these products, and market opportunities to ensure a strategic position among similar products. The study used structural-logical and causal methods of analysis to determine the structure of the novelty of goods. The numerical method of multi-criteria decision making TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) was used to rank the product range of new products according to the level of importance of novelty. Weights of individual components to assess the importance level of novelty in the enterprise were determined by the method of analysis of hierarchies of T.L. Saati. The study used the classification of novelty by its functional focus, according to which consumer, market, and manufacturing novelty of goods are distinguished. The importance of novelty for the manufacturer is the conformity of the product to its innovative development strategy, determination of its place in the market, and prospects for further activities. The importance of the novelty of a new product for the company is proposed to be defined as a measure of the importance of the novelty level of the product for the development of the optimal product range in the product innovative policy of the enterprise. To assess the level of significance of the novelty of goods, criteria of novelty by its types were proposed. According to the results of the study it was found that industrial novelty characterizes the level of use of new technologies in the enterprise, market – the position of a new product on the market among analogues, and consumer – the level and way to meet consumer needs. Further research should relate to the development of appropriate guidelines for the formation of product range and its management based on the assessment of the level of significance of novelty.
Keywords: novelty; level of novelty; level of novelty importance; novelty importance; product innovative policy; новизна; значущість новизни; ступінь новизни; рівень значущості новизни; товарна інноваційна політика; кафедра економіки праці та менеджменту; кафедра маркетингу; кафедра вищої математики імені проф. Можара В. І.